Design and Analysis Unified Resource Management Platform of Grid Dispatching System Based on Virtualization Technology - Ji Zhixiang; Yuan Rongchang; Li Lixin; Di Fangchun; Xie Tao; Dai Jiao (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
As the command center of Strong Smart Grid, the safe and stable operation of the power grid dispatching automation system is the firm guarantee of electric power supply. And dispatching platform is the foundation platform of the power grid dispatching automation system. To make full use of the computing resources and enhance the availability and flexibility of system, this paper puts forward the construction of uniform resource management platform for power grid dispatching automation system based on virtualization technology, thus to provide required computation, storage, network and other resources. With the introduction of virtualization technology including server virtualization, storage virtualization, network virtualization and other technologies, and the construction of corresponding resource pool, the paper designs uniform resources management platform based on virtualization technology and provides new architecture for power grid dispatching automation system. The new system can allocate  and dispatch the resources as a whole, thus to enhance the availability and flexibility of system and realize on-demand allocation and high efficient utilization of resources. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4569